New and critically endangered Sun Moth species associated with Australian grasslands (Lepidoptera, Castniidae) - Kallies, Axel; Edwards, Edward D. (Zootaxa, 2025)
Sun moths are a group of medium sized to large cossoid moths that are relatively species-rich in Australia. Although they are day-flying and colourful and resembe butterflies, they are relatively poorly known. In this study, we examine sun moths of the Synemon collecta Swinhoe, 1892 species group. First, we redescribe and review the distribution of Synemon collecta. We then describe five new species, including Synemon kunama spec. nov. (Snowy Mountains Sun Moth), Synemon yimanorum spec. nov. (Taroom Sun Moth), Synemon gunggariensis spec. nov. (Gunggari Sun Moth), Synemon septentrionalis spec. nov. (Northern Striated Sun Moth), and Synemon striolata spec. nov. (White-veined Sun Moth). Finally, we discuss the conservational status of species of the Synemon collecta group, all of which are associated with remnant grasslands or open grassy woodlands in Australia. Overall, our study emphasises the diversity of lepidopterans associated with Australian grasslands and highlights the urgent need to protect them.